Shadow Labour Market and Labour Law in Russia (to the Question of New Labour Code) - Светлана Юрьевна Барсукова (Journal of Economic Sociology, 2010)
A new labour Code was accepted in the country. Should we expect other labour practices from Russians? Is it able to shrink the shadow labour market? What strategies of decreasing the shadow employment are in this labour code? Do the authorities aspirations correspond to the people’s expectations. How loyal are the people themselves to the shadow labour market? The paper deals with the issues of labour law and analyzes the ability of the new Labour Code to restrain the shadow processes and the people readiness to support the authorities’ intentions or to stay for the illegal labour practices.  The author compares the two versions of the Labour Code projects – the one from the government and that one from trade unions.